Vaccination With a FAT1-Derived B Cell Epitope Combined With Tumor-Specific B and T Cell Epitopes Elicits Additive Protection in Cancer Mouse Models - Grandi, Alberto; Fantappiè, Laura; Irene, Carmela; Valensin, Silvia; Tomasi, Michele; Stupia, Simone; Corbellari, Riccardo; Caproni, Elena; Zanella, Ilaria; Isaac, Samine J.; Ganfini, Luisa; Frattini, Luca; et al. (Frontiers in Oncology, 2018)
Human FAT1 is overexpressed on the surface of most colorectal cancers (CRCs) and in particular a 25 amino acid sequence (D8) present in one of the 34 cadherin extracellular repeats carries the epitope recognized by mAb198.3, a monoclonal antibody which partially protects mice from the challenge with human CRC cell lines in xenograft mouse models. Here we present data in immune competent mice demonstrating the potential of the D8-FAT1 epitope as CRC cancer vaccine. We first demonstrated that the mouse homolog of D8-FAT1 (mD8-FAT1) is also expressed on the surface of CT26 and B16F10 murine cell lines. We then engineered bacterial outer membranes vesicles (OMVs) with mD8-FAT1 and we showed that immunization of BALB/c and C57bl6 mice with engineered OMVs elicited anti-mD8-FAT1 antibodies and partially protected mice from the challenge against CT26 and EGFRvIII-B16F10 cell lines, respectively. We also show that when combined with OMVs decorated with the EGFRvIII B cell epitope or with OMVs carrying five tumor-specific CD4+ T cells neoepitopes, mD8-FAT1 OMVs conferred robust protection against tumor challenge in C57bl6 and BALB/c mice, respectively. Considering that FAT1 is overexpressed in both KRAS+ and KRAS- CRCs, these data support the development of anti-CRC cancer vaccines in which the D8-FAT1 epitope is used in combination with other CRC-specific antigens, including mutation-derived neoepitopes.